2008
DOI: 10.1016/j.ymeth.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of neural lineage cells from human pluripotent stem cells

Abstract: Human pluripotent stem cells have the unique properties of being able to proliferate indefinitely in their undifferentiated state and to differentiate into any somatic cell type. These cells are thus posited to be extremely useful for furthering our understanding of both normal and abnormal human development, providing a human cell preparation that can be used to screen for new reagents or therapeutic agents, and generating large numbers of differentiated cells that can be used for transplantation purposes. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 126 publications
0
44
0
Order By: Relevance
“…The same effect is observed for the EBs generated using the 4-/4+ protocol, suggesting that the effects on differentiation take longer in the miPSC-derived EBs. While iPSCs and ESCs use the same signalling pathways when differentiating into neural phenotypes, high variability in differentiation efficiency is observed between different cell lines, regardless of whether they are iPSCs or ESCs [7,12,49]. Thus, it may be possible to attribute the differences between the miPSC-and mESC-derived EBs to differences between the specific cell lines rather than as representing general differences between iPSCs and ESCs.…”
Section: 23mentioning
confidence: 99%
“…The same effect is observed for the EBs generated using the 4-/4+ protocol, suggesting that the effects on differentiation take longer in the miPSC-derived EBs. While iPSCs and ESCs use the same signalling pathways when differentiating into neural phenotypes, high variability in differentiation efficiency is observed between different cell lines, regardless of whether they are iPSCs or ESCs [7,12,49]. Thus, it may be possible to attribute the differences between the miPSC-and mESC-derived EBs to differences between the specific cell lines rather than as representing general differences between iPSCs and ESCs.…”
Section: 23mentioning
confidence: 99%
“…Since then, MSCs have been isolated from many other adult tissues such a umbilical cord blood, placenta, amniotic fluid, peripheral blood, adipose tissue and various other somatic tissues sharing the regenerative as well as the immunomodulatory properties of MSCs (In 't Anker, Scherjon et al 2004;Zuk 2010;Bianco 2011) but have mainly been characterized after isolation from bone marrow. MSCs can be expanded in vitro as plastic adherent cells with a fibroblast-like morphology and can be differentiated into cells of mesodermal lineage (osteocytes, chondrocytes and adipocytes) (Pittenger, Mackay et al 1999) as well as cells from other embryonic lineages (Sanchez-Ramos 2006;Schwartz, Brick et al 2008). At present, MSCs lack a definitive marker and no single marker has been identified distinguishing MSCs however the International Society for Stem Cell Research has outlined minimal criteria to characterize human MSCs, these cells have been reported to be positive for CD73, CD90, CD105 and major histocompatibility complex class I (HLA-ABC).…”
Section: The Biology and Originality Of Mesenchymal Stem Cells And Thmentioning
confidence: 99%
“…In a review article on neural cell differentiation methods Schwartz et al (2008) showed many variations in the use of the materials to induce the differentiation of mesenchymal cells into neural cells. FGF and EGF have important role in the maintenance and expansion of differentiated cells (Schwartz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…FGF and EGF have important role in the maintenance and expansion of differentiated cells (Schwartz et al 2008). What is important is none of the methods was used to induce the hUCMs differentiation into neural cells.…”
Section: Introductionmentioning
confidence: 99%